2017
DOI: 10.21767/2254-6081.1000148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of FTO SNPs rs9930506 and rs9939609 in Prostate Cancer Severity in a Cohort of Puerto Rican Men

Abstract: Background Obesity is prevalent in PR and has been associated with prostate cancer (PCa) mortality and aggressiveness. Polymorphisms (SNPs) rs9930506 and rs9939609 in the FTO gene have been associated with both obesity and PCa. The aim of this work was to ascertain whether the presence of these SNPs is associated with PCa risk and severity in a cohort of Puerto Rican men. Methods and findings The study population consisted of 513 Puerto Rican men age ranging from 40–79 years old who underwent radical prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Although the association of the FTO rs9939609 polymorphism with PCa risk was weak in all previous studies, and might depend on different confounding factors, the meta-analysis performed in this study confirmed a strong and consistent association of this intronic variant with a decreased risk of PCa. A recent study also demonstrated that the association of the FTO rs9939609 SNP with a decreased risk of PCa was found in non-European populations, and that the presence of this genetic marker tended to be associated with disease severity in patients that were overweighted [89]. These findings, together with the lack of significant results in our functional studies, suggest that the role of the FTO locus in determining PCa might be mediated by complex obesogenic and/or diabetogenic mechanisms.…”
Section: Discussionsupporting
confidence: 69%
“…Although the association of the FTO rs9939609 polymorphism with PCa risk was weak in all previous studies, and might depend on different confounding factors, the meta-analysis performed in this study confirmed a strong and consistent association of this intronic variant with a decreased risk of PCa. A recent study also demonstrated that the association of the FTO rs9939609 SNP with a decreased risk of PCa was found in non-European populations, and that the presence of this genetic marker tended to be associated with disease severity in patients that were overweighted [89]. These findings, together with the lack of significant results in our functional studies, suggest that the role of the FTO locus in determining PCa might be mediated by complex obesogenic and/or diabetogenic mechanisms.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, FTO rs9939609, which was a SNP known to be associated with obesity, was inversely related with low-grade prostate cancer risk, but positively related with high-grade prostate cancer. Salgado-Montilla et al 30 also discovered the same correlation between FTO rs9939609 and prostate cancer risk; nonetheless, the result was not statistically significant upon adjustment.…”
Section: Fto Single Nucleotide Polymorphism (Snp) With Cancer Riskmentioning
confidence: 87%
“…Single-nucleotide polymorphisms (SNPs) in FTO was identified and not associated with body mass index (BMI), but was associated with melanoma risk in the first report in 2013 (21). However, it has been reported that rs9939609 polymorphism in the FTO gene is associated with a risk of breast and prostate cancer (22). Both genetic changes and FTO expression are thought to be involved in the biological process of cancer.…”
Section: Discussionmentioning
confidence: 99%